Evaluasi Penerimaan Masyarakat Terhadap Aplikasi Telemedicine pada Masa Pandemi COVID-19 - Muhammad Reza Velayani; Muhammad Taufiq Nuruzzaman; Agung Fatwanto; Bambang Sugiantoro (JISKA (Jurnal Informatika Sunan Kalijaga), 2023)
Telemedicine is a technology that provides benefits during the COVID-19 pandemic, which has been going on for more than two years. However, we have never conducted an evaluation or assessment of Telemedicine applications. In this study, we tried to look at people's acceptance of using the application, and 104 participants became respondents. This study uses the TAM (Technology Acceptance Model) method, which this method measures the influence between variables. TAM has five indicator variables: Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, Behavioral Intention, and Actual Usage. In this study, four models were made with three comparison models; then, for the results of testing the relationship between variables, three hypotheses are always accepted in each model, namely Perceived Ease of Use with Perceived Usefulness, Perception Ease of Use with Attitude Toward Using, and Behavioral Intention with Actual Usage. Then the two hypotheses always rejected in each model are Perceived Usefulness with Attitude Toward Using, Attitude Toward Using with Behavioral Intention. Then there is one hypothesis for each model that is refused, namely Perceived Usefulness with Behavioral Intention, Perceived Usefulness with Actual Usage, Perceived Ease of Use with Behavioral Intention, and Perceived Ease of Use with Actual Usage.